Domination Portrayal in Sing Movie by Garth Jannings: Symbolic Violence Analysis - Sukmawati Sukmawati; M. Amir P; Herawaty Abbas (Hasanuddin University, 2022)
This article discusses about symbolic violence in Sing movie. Sing is a 3D animation movie produced by Illumination Entertainment 2016. The characters are animals that act like human with the specific characterization. The reason for choosing this movie because it is much entertaining, and it actually obtained the symbolic violence through its characters. This study is aimed to analyze the issue of symbolic violence, which is usually carried out by the superior owners to dominate people who don’t have power. This study is related to Pierre Bourdieu's theory called symbolic violence. The method of this study is descriptive qualitative. The data were collected through process of watching, pausing and interpreting and then the writer analyzed those data by using the theory of symbolic violence by Pierre Bourdieu. The result of the study shows that the forms of symbolic violence that are symbolic violence of superior to inferior (England to America), symbolic violence of family to children (Big daddy to Johnny), symbolic violence male to female (Rosita’s husband to Rosita), (Lance to Ash), (Grandfather to Meena), (Garth Jennings to Miss Crawly), and symbolic violence between the upper and lower classes (Superior to Jews). The writer concluded that England wanted to show that the super power countries in the world were England, not America. America gets strength from England and also America will not succeed if there is no Asia. Asia has an important role in making America successful and, getting recognition from the England.